2020
DOI: 10.1038/s41598-020-75085-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrin alpha V (ITGAV) expression in esophageal adenocarcinoma is associated with shortened overall-survival

Abstract: Valid biomarkers for a better prognostic prediction of the clinical course in esophageal adenocarcinoma (EAC) are still not implemented. Integrin alpha V (ITGAV), a transmembrane glycoprotein responsible for cell-to-matrix binding has been found to enhance tumor progression in several tumor entities. The expression pattern and biological role of ITGAV expression in esophageal adenocarcinoma (EAC) has not been analyzed so far. Aim of the study is to evaluate the expression level of ITGAV in a very large collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…Integrin alpha V ( ITGAV ), a transmembrane glycoprotein, has been found to enhance tumor progression. ITGAV expression is associated with shortened overall survival in esophageal adenocarcinoma 34 . Genes ITGAV, FN1 , and ITGB1 were shown to be the targets of miR-9-3p, which could inhibit proliferation and metastases of nasopharyngeal carcinoma by downregulating FN1, ITGB1 , and ITGAV , thus inhibiting the EMT process 35 .…”
Section: Discussionmentioning
confidence: 96%
“…Integrin alpha V ( ITGAV ), a transmembrane glycoprotein, has been found to enhance tumor progression. ITGAV expression is associated with shortened overall survival in esophageal adenocarcinoma 34 . Genes ITGAV, FN1 , and ITGB1 were shown to be the targets of miR-9-3p, which could inhibit proliferation and metastases of nasopharyngeal carcinoma by downregulating FN1, ITGB1 , and ITGAV , thus inhibiting the EMT process 35 .…”
Section: Discussionmentioning
confidence: 96%
“…Integrin alpha V (ITGAV), a transmembrane glycoprotein, has been found to enhance tumor progression. ITGAV expression is associated with shortened overall survival in esophageal adenocarcinoma 33 . Genes ITGAV, FN1, and ITGB1 were shown to be the targets of miR-9-3p, which could inhibit proliferation and metastases of nasopharyngeal carcinoma by downregulating FN1, ITGB1, and ITGAV, thus inhibiting the EMT process 34 .…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have shown that ITGAV is highly expressed in osteosarcoma, hepatocellular carcinoma, and oesophageal adenocarcinoma tissues compared to normal tissues. 51 , 52 , 53 Additionally, inhibition of ITGAV has been shown to reduce tumour growth and metastasis in a variety of cancers. 54 , 55 , 56 Herein, we observed that ITGAV was highly expressed in human ESCC tissues (Figure 1A–C ) and that increased ITGAV levels were related with poor overall survival (Figure 1D ).…”
Section: Discussionmentioning
confidence: 99%